Contraceptive uptake and compliance after structured contraceptive counseling ‐ secondary outcomes of the LOWE trial - Isabella Bizjak; Niklas Envall; Karin Emtell Iwarsson; Helena Kopp Kallner; Kristina Gemzell‐Danielsson (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Highly effective long‐acting reversible contraceptive (LARC) methods reduce unintended pregnancy rates; however, these methods are underutilized. The LOWE trial intervention provided structured contraceptive counseling resulting in increased uptake of LARC. This longitudinal follow up of the LOWE study assessed the long‐term impact of the intervention by investigating the contraceptive use at 12 months with a focus on continued use of LARC. Material and methods In the cluster randomized LOWE trial, abortion, youth, and maternal health clinics were randomized to provide either structured contraceptive counseling (intervention) or standard contraceptive counseling (control). The intervention consisted of an educational video on contraceptive methods, key questions asked by the health care provider, a tiered effectiveness chart and a box of contraceptive models. Women ≥ age 18, who were sexually active or planned to be in the upcoming 6 months, could participate in the study. We assessed self‐reported contraceptive use at three, six and 12 months. Contraceptive choice and switches were analyzed with descriptive statistics. Contraceptive use at 12 months and continued use of LARC were analyzed using mixed logistic regressions, with clinic included as a random effect. Analysis with imputed values were performed for missing data to test the robustness of results. Results Overall, at 12 months, women in the intervention group were more likely to be using a LARC method (aOR 1.90, 95% CI: 1.31–2.76) and less likely to be using a short‐acting reversible contraceptive (SARC) method (aOR 0.66, 95% CI: 0.46–0.93) compared to the control group. Women counseled at abortion (aOR 2.97, 95% CI: 1.36–6.75) and youth clinics (aOR 1.81, 95% CI: 1.08–3.03) were more likely to be using a LARC method, while no significant difference was seen in maternal health clinics (aOR 1.84, 95% CI: 0.96–3.66). Among women initiating LARC, continuation rates at 12 months did not differ between study groups (63.9% vs. 63.7%). The most common reasons for contraceptive discontinuation were wish for pregnancy, followed by irregular bleeding, and mood changes. Conclusions The LOWE trial intervention resulted in increased LARC use also at 12 months. Strategies on how to sustain LARC use needs to be further investigated.